2000
DOI: 10.4315/0362-028x-63.9.1214
|View full text |Cite
|
Sign up to set email alerts
|

Viability and β-Galactosidase Activity of Dairy Propionibacteria Subjected to Digestion by Artificial Gastric and Intestinal Fluids

Abstract: An important criterion to consider in the selection of strains for dietary adjuncts is the ability of the microorganisms to survive the severe conditions of acidity and bile concentrations usually found in the gastrointestinal tract. In the present work, we report the effects of digestions by artificial gastric and intestinal fluids on beta-galactosidase activity and survival of four strains of dairy propionibacteria previously selected by their bile tolerance and beta-galactosidase activity. The strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 30 publications
7
82
1
3
Order By: Relevance
“…It has also been demonstrated that the vehicle used for delivery of probiotics is important for digestive stress tolerance since cells included in food matrices like milk or cheese had better tolerance to acid challenge than free cultures [132]. Similar results were obtained by Huang and Adams [134], by protecting propionibacteria from acid and bile stresses with a soymilk and cereal beverage, and Leverrier et al [136], who used yoghurt-type fermented milk.…”
Section: Safety and Persistence In The Gutsupporting
confidence: 73%
See 3 more Smart Citations
“…It has also been demonstrated that the vehicle used for delivery of probiotics is important for digestive stress tolerance since cells included in food matrices like milk or cheese had better tolerance to acid challenge than free cultures [132]. Similar results were obtained by Huang and Adams [134], by protecting propionibacteria from acid and bile stresses with a soymilk and cereal beverage, and Leverrier et al [136], who used yoghurt-type fermented milk.…”
Section: Safety and Persistence In The Gutsupporting
confidence: 73%
“…However there are no clinical reports on this property for dairy propionibacteria. Several evidences suggest the potential of Propionibacterium acidipropionici strains on this subject: they have high β-galactosidase activity that remain unaltered in the conditions of the human's intestine, and cells are permeabilized by bile, which in turn may favour the hydrolysis of lactose within the intestine [131,132]. Besides, the manufacture conditions of Swiss-type cheese did not decrease the synthesis and activity of the β-galactosidase of these propionibacteria [197].…”
Section: Modulation Of the Host And Resident Microbiota Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they were able to down-regulate the carcinogenic β-glucuronidase, azoreductase and nitroreductase activities in these animals [23]. Propionibacteria were also shown to be a source of β-galactosidase, which would be liberated as a result of bile salts permeabilisation within the gut [32]. They could thus be useful to prevent lactose intolerance.…”
Section: Introductionmentioning
confidence: 99%